2022
DOI: 10.1371/journal.pwat.0000007
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing a routine wastewater monitoring laboratory for SARS-CoV-2

Abstract: Wastewater-based testing for SARS-CoV-2 is a novel tool for public health monitoring, but additional laboratory capacity is needed to provide routine monitoring at all locations where it has the potential to be useful. Few standardization practices for SARS-CoV-2 wastewater analysis currently exist, and quality assurance/quality control procedures may vary across laboratories. Alongside counterparts at many academic institutions, we built out a laboratory for routine monitoring of wastewater at the University … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 21 publications
4
28
0
Order By: Relevance
“…A possible dilution caused by inflow of rainwater can be calculated by measuring concentration of pepper mild mottle virus (PMMoV) in the sample and normalizing the SARS-CoV-2 gene copies to PMMeV gene copies. PMMeV is a fecal biomarker present in human feces through diet [25], [26]. For this pilot project, we did not take possible rainwater infiltration into account.…”
Section: Discussionmentioning
confidence: 99%
“…A possible dilution caused by inflow of rainwater can be calculated by measuring concentration of pepper mild mottle virus (PMMoV) in the sample and normalizing the SARS-CoV-2 gene copies to PMMeV gene copies. PMMeV is a fecal biomarker present in human feces through diet [25], [26]. For this pilot project, we did not take possible rainwater infiltration into account.…”
Section: Discussionmentioning
confidence: 99%
“…This is a significant problem because under-reporting may lead to a false sense of security among the public and hinder data-driven decisions by policymakers. Overall, this study indicates the need to continue regular surveillance and heed the warnings of viral genome concentrations in the wastewater as a representative indicator of community health as well as COVID-19 cases in the area [6,[30][31][32][33]. Smaller communities do not always have access to the same resources or information available in larger cities.…”
Section: Discussionmentioning
confidence: 92%
“…Third, we have found that results of long term-monitoring using RT-qPCR may be subject to plate-to-plate fluctuations due to differences in standard curve serial dilutions (29). While standard curve efficiency and R 2 are key components of quality control, the y-intercept should also be monitored as an indicator of standard degradation or batch differences.…”
Section: Discussionmentioning
confidence: 99%
“…Data analysis was performed using Python (v3.9.5) using modules Pandas (v1.2.5), NumPy (v1.21.0), SciPy (v1.7.0), and Plotnine (v0.8.0). RT-qPCR analysis of standard curves and unknowns was performed using custom code as previously described (29) (https://github.com/wastewaterlab/data_analysis). Pearson correlation coefficients were determined using SciPy, and linear regressions were conducted using NumPy polyfit.…”
Section: Methodsmentioning
confidence: 99%